The Influence of Water and Gas Exchange Parameters on Grafted Grapevines Under Conditions of Moisture Stress - Satisha, J.; Prakash, G.S. (South African Journal of Enology and Viticulture, 2017)
Among the four grape varieties that were subjected to moisture stress, Flame Seedless and Thompson Seedless recorded the highest relative water content, osmotic potential and water potential compared to Sharad Seedless and Tas-A-Ganesh. Similarly, Flame Seedless and Thompson Seedless recorded the maximum rate of photosynthesis, the minimum transpiration rate, and thus increased water-use efficiency. Sharad Seedless on its own root had the lowest water-use efficiency. Budding the respective four varieties on different rootstocks and subjecting them to moisture stress resulted in significant differences in various physiological parameters that influence water-use efficiency. When Sharad Seedless was budded on Dog Ridge rootstock and subjected to moisture stress, it resulted in increased water potential, osmotic potential and water use efficiency compared to other rootstocks. This suggests that rootstocks have an influence on the physiological mechanisms of scion leaves. Hence, the genotypic selection of rootstocks for establishing vineyards under drought conditions is of great importance